Effect of neoadjuvant chemotherapy on tumor immune infiltration in breast cancer patients: Systematic review and meta-analysis - Manuela Llano-León; Laura Camila Martínez-Enriquez; Oscar Mauricio Rodríguez-Bohórquez; Esteban Alejandro Velandia-Vargas; Nicolás Lalinde-Ruíz; María Alejandra Villota-Álava; Ivon Johanna Rodríguez-Rodríguez; María del Pilar Montilla-Velásquez; Carlos Alberto Parra-López (PLoS ONE, 2023)
The tumor immune infiltrate has an impact on cancer control and progression, additionally a growing body of evidence has proposed the role of neoadjuvant chemotherapy in modulating the contexture of the tumor immune infiltrate. Here, we performed a systematic review to evaluate the effect of chemotherapy in the immune infiltration of breast cancer tumors. We systematically searched Pubmed/MEDLINE, EMBASE, CENTRAL, and BVS databases with a cutoff date of 11/06/2022. Studies in patients with pathological diagnosis of BC, whose first line of treatment was only NAC, were included. Only published experimental studies that measured tumor immune infiltrate before and after NAC by hematoxylin and eosin (H&E) staining, immunohistochemistry (IHQ), or transcriptome were included. Reviews, studies with animal models and in-vitro models were excluded. Studies in which BC was not the primary tumor or studies with patients who received other types of neoadjuvant therapy were also excluded. The NIH quality assessment tool for before and after studies without control was used. We included 32 articles that evaluated the proximal tumor microenvironment before and after neoadjuvant chemotherapy in 2072 patients who received NAC as first line of treatment and who were evaluated for immune infiltrate in the pre- and post-chemotherapy tumor sample. Results were divided into two major categories immune cells and in-situ expression of immune checkpoints and cytokines. Qualitative synthesis was performed with the 32 articles included, and in nine of them a quantitative analysis was achieved, resulting in six meta-analyses. Despite high heterogeneity among the articles regarding treatment received, type of tumor reported, and techniques used to evaluate immune infiltrate, we found a significant decrease of TILs and FoxP3 expression after neoadjuvant chemotherapy. The study protocol was registered in PROSPERO 2021 (Protocol ID: CRD42021243784) on 6/29/2021.